Different honesty conceptions align across US politicians' tweets and public replies - Fabio Carrella; Segun T. Aroyehun; Jana Lasser; Almog Simchon; David Garcia; Stephan Lewandowsky (Nature Communications)
Abstract Recent evidence shows that US politicians’ conception of honesty has undergone a bifurcation, with authentic but evidence-free “belief-speaking” becoming more prominent and differentiated from evidence-based “fact-speaking”. Here we examine the downstream consequences of those two ways of conceiving honesty by investigating user engagement with fact-speaking and belief-speaking texts by members of the US Congress on Twitter (now X). We measure the conceptions of honesty of a sample of tweets and replies using computational text processing, and check whether the conceptions of honesty in the tweets align with those in their replies. We find that the conceptions of honesty used in replies align with those of the tweets, suggesting a “contagion”. Notably, this contagion replicates under controlled experimental conditions. Our study highlights the crucial role of political leaders in setting the tone of the conversation on social media.